2020
DOI: 10.21203/rs.3.rs-29053/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chatuphalatika, a Thai herbal formula, ameliorate obesity and dyslipidemia in high-fat diet fed mice

Abstract: Background Chatuphalatika is a Thai traditional health tonic composing of four different herbs namely Terminalia bellerica Linn., T. chebula Retz., T. arjuna Roxb. and Phyllanthus emblica Linn. The fact that phytoconstituents of Terminalia species have been reported to ameliorate obesity and symptoms of metabolic syndrome prompt us to investigate acute toxicity as well as a lipid lowering activity of orally given chatuphalatika aqueous extract (CPT) in animal models. Methods CPT was prepared by decoction met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…JPT is well known for its antioxidant activity, and it is used as an antipyretic, laxative, stomachic, colon cleanser, detoxifying agent, health promotion agent, and rejuvenator in Tai traditional medicine [13,14]. Scientifc evidence has revealed that JPT has antimutagenic, cardioprotective, radioprotective, hepatoprotective, anti-infammatory, and antiobesity properties [15,16]. In addition, the TSM and JPT recipes consist of numerous secondary metabolites such as favones, alkaloids, phenols, tannins, coumarin, terpenoids, glycosides, and saponins [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…JPT is well known for its antioxidant activity, and it is used as an antipyretic, laxative, stomachic, colon cleanser, detoxifying agent, health promotion agent, and rejuvenator in Tai traditional medicine [13,14]. Scientifc evidence has revealed that JPT has antimutagenic, cardioprotective, radioprotective, hepatoprotective, anti-infammatory, and antiobesity properties [15,16]. In addition, the TSM and JPT recipes consist of numerous secondary metabolites such as favones, alkaloids, phenols, tannins, coumarin, terpenoids, glycosides, and saponins [17][18][19].…”
Section: Introductionmentioning
confidence: 99%